Accommodative extractor for QIM‐based watermarking schemes. Issue 1 (1st January 2019) - Kricha, Zied; Kricha, Anis; Sakly, Anis
Abstract : In quantisation index modulation‐based watermarking methods, each host coefficient is replaced by an adequate quantiser according to the embedded bit. However, after the attack, the distribution of the hosts does not remain the same, resulting in a failure to map coefficients to their correct bits. To maintain a good quality, many authors focused on improving the extraction, rather than playing on the embedding parameters. They used a reference message to define the parameters of the channel model after the attack. However, the available solutions were not effective, whereas the reference message cannot describe the channel alteration due to a shortage of samples, and the complexity of attacks modelling. To overcome these problems, the authors relied on a diversification technique, which allowed to enlarge and vary the samples. Then, based on quantisation embedding rules, they generated an accommodative detection model for each attack. At the extraction phase, the suitable detection model was identified by means of a reference message. To reinforce the security of their scheme, the watermark was initially shuffled, which prevents any unauthorised detection attempt. Both geometric and signal processing attacks were used in the validation of their method. The reduction of bit‐error rate with respect to the conventional detection method reached up to 100%.